Fragmentation of trimethylsilyl derivatives of 2-alkoxyphenols: a further violation of the ‘even-electron rule’ - Krauß, Dietlinde; Mainx, Hans-Georg; Tauscher, Bernhard; Bischof, Peter (Organic mass spectrometry, 1985)
The mass spectra of trimethylsilyl (TMS) ethers of 2-methoxyphenols show abundant [M-30]+˙ ions originating from consecutive loss of two methyl radicals. This is illustrated by comparison of the accurate mass-measured and linked-scan spectra of the TMS derivatives of 2-methoxyphenol (guaiacol), 4-hydroxy-3-methoxybenzaldehyde (vanillin) and 3-(4-hydroxy-3-methoxyphenyl)-2-propenoic acid methyl ester (ferulic acid methyl ester) with those of the TMS derivatives of phenol, 4-hydroxybenzaldehyde, 3-(4-hydroxyphenyl)-2-propenoic acid methyl ester (p-coumaric acid methyl ester), 3-methoxyphenol and 4-methoxyphenol. This distinctive ortho effect is valuable in the identification of isomeric phenolic compounds. In the spectra of the TMS derivatives of 2-ethoxyphenol and 2-propoxyphenol the sequential loss of two radicals is less pronounced, because elimination of the side-chain and a methyl group with rearrangement and hydrogen migration is competitive.
Gesehen am 16.12.2025